Effects of management and structural connectivity on the plant communities of organic vegetable field margins in South Korea. Issue 6 (27th September 2013) - Kang, Wanmo; Hoffmeister, Mathias; Martin, Emily A.; Steffan‐Dewenter, Ingolf; Han, Donguk; Lee, Dowon
Abstract: Field margins are an important component of the agri‐environment as they contribute to maintaining ecosystem functions and protecting biodiversity. Field margin structure, landscape attributes, and management practices have been examined as determinants of plant species diversity and composition for mainly cereal field margins; however, relatively little is known about their influence on vegetable field margins. We selected three types of field margins (each n = 4; non‐managed connected to forests, non‐managed isolated, and isolated and managed margins with mowing and organic herbicide) adjacent to organic vegetable crop fields and recorded the species richness and abundance of all vascular plants. The effects of structural connectivity, weed control management, and margin width on the community composition, species richness, and diversity were examined using multivariate statistical techniques. Plant community composition was clearly explained by structural connectivity between field margin and forest, as well as by weed control management. In contrast, species richness of functional guilds was influenced by connectivity and margin width, but not by weed control management. All communities had similar numbers of summer and fall blooming nectar‐ and pollen‐producing plants, an important source of pollination services. In addition, each community of field margin types, despite different species composition, had similar levels of Shannon diversity and evenness. Our results suggest that habitat arrangement is important for determining community composition in field margins. Management practices may be important in determining dominance patterns of individual species. A combination of various margin types and widths may be beneficial for biodiversity conservation and ecosystem services.